Hard kill [videorecording (DVD)] - Eskandari, Matt; LaMont, Chris; Willis, Bruce, 1955-; Metcalfe, Jesse, 1978-; Rizzuto, Sergio; Kent, Lala (Lions Gate Home Entertainment, 2020)
When a billionaire tech CEO hires a team of mercenaries to protect a lethal piece of technology, the security expert and his team must race against the clock to protect the fate of the human race.